The Art and the Science of Manuscript Publication: Tips and Tricks for Health Science Students and Professionals - Waqar M. Naqvi1 , Chanan V. Goyal2, Arti Sahu3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Health care professionals are bound by the duty of providing the best possible care to their clients. To abideby this, one needs to constantly learn and imbibe the advances in the field. Evidence-based practise shouldbe built on the firm foundation of evidence synthesis. A professional may be a clinician, an academician, ora researcher per se, but contribution to the evolution of their profession is an indispensable responsibility.Conducting research is a scientific process which when combines with the art of writing the manuscriptinfluences innumerable lives in more than one positive way. Publication of findings not only helps one inprofessional development but also helps others globally in upgrading their services to benefit humankind.The process of drafting and publishing a manuscript needs initial guidance that appears to be missing as amajor part in the health science curriculum. In this article, we aim to outline the practical points to facilitatethe process of writing a manuscript for publication. This article includes the information on types of acceptedarticles, the pattern of manuscripts, gold standard guidelines, tips to draft each section of the manuscript(including cover letter), and how to choose a journal for publication, which would help to reduce the timerequired to prepare a draft and to increase the probability of acceptance of the manuscript for publication.